The role of the auditor in studying and evaluating the internal control system and its impact on determining the size of the audit sample: (An analytical study in the Directorate of Education of Najaf Governorate) - Hatim Karem Kadom; Razaq Sadeq Razaq (Iraqi Journal for Administrative Sciences, 2025)
Internal Control is the Starting Point when The prepares Audit Program and determine the Volume of The Examinations and Tests be Area for The Application of Audit Procedures The Auditor must therefore be Informed and Fully aware of the Strength or Weakness of The Internal Control System and work on the Study and Evaluation. If the Internal Control System is Strong and Solid, The Auditor shall reduce the Volume of The Tests and Whether The Internal Control System is Weak shall Increase The Volume of Tests when using The Style of The Sample Statistics, but if does not have A auditor to Study and Evaluate The Internal Control System, it means there are Gaps in The Accounting System and Mean The increase of Embezzlement , Theft and Fraud, so this Study was focused on The Necessity of having The auditor a clear Vision about The Nature of The Internal Control System Applied in Economic Unit, and identify Weaknesses or Strengths in order to possess The ability to select and determine The Volume of The Sample Audit Correctly and Appropriately, and thereby to reduce Errors and Risk, which is Located on The Auditor's Responsibility for that Summarized The Research Problem not taking into Account The Strength or Weakness of The Internal Control System Applied to the Sample Unit when determining The Volume of The Sample Audit by The auditor. The Objective of this Research is to identify the most Important effects that can be induced Strength or Weakness of The Internal Control System to determine the Volume of The Sample Audit in the Economic Units and Description and Diagnosis ,Independent and Dependent Research Variables and represent of Internal Control System and The Volume of The Sample Audit and analysis of The Correlation Relationship between The Variables of Research. The Research has come to a set of Conclusions and Recommendations represent the most Conclusions: The Showing of Search Results through Statistical Analysis of that Internal Control System Variable got on The Weight of a relative amount (69.866%) and Coefficient of Variation (25.824%), While the Volume of The Sample Audit obtained on the weight of a relative (80.132%) and Coefficient of Variation ( 25.629%) and the back of this clear from the answers of the Research Sample, and revealed the Results of the search for A correlation Strong and Positive between The Independent Variable (the Internal Control System) and The Dependent Variable (The Volume of The Sample Audit), amounting to (0.965) through the Simple Correlation Coefficient. The amount Coefficient of Linear Regression (1.098 = ) at the abstract level (5%), which demonstrates the effect of the Internal Control System Variable to determine the Volume of The Sample Audit, while the Value of Coefficient of determination (R2) of (0.931) is able to explain what Percentage of (93.1%) of the changes in the Volume of The Sample Audit, and the remaining amount (6.9%) is attributable to the Contribution of Other Variables. The most Important Recommendations are: it is necessary to have an Auditor Expertise and Sufficient Experience in the use of Statistical Methods in the Selection of Sample Volume, Verification of the Objectives developed by the Management of Economic Unit in the Internal Control System to protect Assets from Theft, Embezzlement, Fraud, and the need for attention, Department of Internal Control through training and rehabilitation of the Staff of this Department, supervision and determine the Degree of Independence.